1996
DOI: 10.1212/wnl.46.1.267
|View full text |Cite
|
Sign up to set email alerts
|

Vomiting out of proportion to dizziness in ischemic brainstem strokes

Abstract: At the onset of ischemic strokes involving the lower brainstem, vomiting may be prominent when dizziness and other neurologic abnormalities are minimal or absent. Errors in interpretation may result in the misdiagnosis of a gastrointestinal disorder. The stroke literature does not clearly refer to this clinical point. The present note draws attention to the phenomenon both for practical diagnostic reasons and to illustrate a distinct form of vestibular vomiting.A 52-year-old hypertensive, diabetic man with a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Vomiting out of proportion to the degree of dizziness may be a marker for central disease. 25 In the present study, nausea and vomiting was observed more frequently in patients with non-AIS, believed to be because a large number of tumours were identified in the S group. No significant association was found between AIS and auditory symptoms, craniocervical pain, previous episodes, or pre-syncope episodes.…”
Section: Discussionsupporting
confidence: 43%
“…Vomiting out of proportion to the degree of dizziness may be a marker for central disease. 25 In the present study, nausea and vomiting was observed more frequently in patients with non-AIS, believed to be because a large number of tumours were identified in the S group. No significant association was found between AIS and auditory symptoms, craniocervical pain, previous episodes, or pre-syncope episodes.…”
Section: Discussionsupporting
confidence: 43%
“…22,24 Our critical review identified some weak evidence to support this contention. Authors of uncontrolled case reports and small case series hypothesized that the presence of vomiting 52,83,84 or imbalance and gait unsteadiness 52 that was out of proportion to the degree of dizziness or nystagmus may be a marker of brainstem or cerebellar pathology, including stroke.…”
Section: Associated Symptoms and Risk Factorsmentioning
confidence: 99%
“…However, other authors consider the presence of a cerebral infarction is one of the most powerful predictive factors recurrent embolism [54-58]. In the study of van Latum et al .…”
Section: Embolic Recurrence In Cardioembolic Infarctionmentioning
confidence: 99%